POSSIBILIDADES DE SOFRIMENTO PSÍQUICO DO PROFESSOR UNIVERSITÁRIO DE UMA LICENCIATURA - Kelly Cristina Tesche Rozendo; Carmen Lúcia Dias (Universidade do Oeste Paulista, 2014)
Teaching work has revealed cases of illness in the workplace. Thinking about it, this research has the general objective to analyze the psychic suffering of university professor of undergraduate, seeking to highlight aspects that make your work environment. Specifically, was checked the conception that Pedagogy undergraduate professors have about teaching; was identified characteristics of the working environment of university professors; was investigated the physical and mental health of these professionals. Using a qualitative approach and case study type, the methodology involved the collection of data, through a questionnaire and interviews semistructured with fourteen professors of the undergraduate in Pedagogy course of a particular Higher Education Institution in the state of São Paulo. The analysis was organized by axes and categories. The results revealed that aspects of the academic work environment may impact on psychic suffering and adversely affecting the health of the university professors.